Radiographic evaluation of hypercementosis in Al-Madinah region, KSA: A retrospective cross sectional study - Shadia A. Elsayed; Yosra Ayed; Albraa B. Alolayan; Lamis M. Farghal; Saba Kassim (Elsevier, 2019)
Background: Hypercementosis (HC) is an excessive cementum deposition at the root apex which is asymptomatic condition that often makes routine tooth extraction difficult. There is a lack of research that evaluates and determines patterns and correlations of hypercementosis in Saudi Arabia. Objectives: The purpose of this study is to retrospectively evaluate HC prevalence, anatomical location, distribution and radiographic characteristics among female patients who attended the dental college and hospital, Taibah University, Al-Madinah Almunawwarah, (KSA) between Jan 2015 and Nov 2017. Methods: A retrospective cross-sectional study was conducted. 815 random digital Orthopantomograms (OPGs) were selected out of 14003 OPGs for the period between Jan 2015 and Nov 2017. The selected sample were retrieved from Kodak Carestream-R4 database at Taibah University Dental College & hospital (TUDCH). Width, length, radiodensity of HC were measured and the anatomical distribution of HC was calculated. Association between HC and factors including age and nationality was investigated. Descriptive and inferential analyses were performed. Results: Among the selected 815 OPGs, 80 (9.8%) roots were affected with HC. The mean age of HC affected patients was 30.16 ± 13.1 years, of whom 55% were Saudis. Mandible was found to be affected twice than maxilla (65%), (35%) respectively. First molars were the most affected teeth (47.5%). The majority of affected teeth had single unilateral distribution pattern (64%). The right side was affected higher than the left side with a percentage of 53% and 47% respectively. The mean width of HC lesion was 4.14 ± 1.2 mm, mean length was 5.2 ± 1.7 mm while the mean radiodensity was 119.86 ± 29.83 pixel intensity. There was no significant correlation between nationality, age and HC (P = 0.921, P = 0.633, respectively). Conclusion: HC has been found in 9.8% of female patients attending TUDCH, which is mainly affecting the mandibular teeth. Oral and maxillofacial surgeons, general dentists and dental students should be aware of the high prevalence of HC among Al-Madinah population in order to anticipate and minimize teeth extraction complications. Recommendation: Further validation of OPGs findings with histological examination and comparison between male and female in different regions of Saudi Arabia (multi-center study) are required. Conflict of interest: The authors declared that there is no conflict of interest. Ethical considerations: The present study was carried out in accordance with The Code of Ethics of the World Medical Association (Declaration of Helsinki). The study was approved by Research Ethical Committee of Taibah University (TUCDREC2Ol7O3O7Farghal). All patients' personal information was not identified and only the researchers had access to the records. Keywords: Hypercementosis, Al Madinah, Tooth